Can the Leibovich score for clear cell renal cell carcinoma (ccRCC) be accurately reported by a general pathologist?. (2nd December 2013) - Vasdev, Nikhil; Altal, Yaman; Mafeld, Sebastian; Wong, Kevin; Chadwick, David; Gowda, Basavaraj D.R.; Mutton, Adrienne; Nagarajan, Srikantiah; Bhatti, Aftab
<x xml:space="preserve">Abstract</x> Objectives To evaluate the accuracy of reporting of the Leibovich score (LS) by general pathologists at our centre by comparing the LS in their initial reports with the LS in subsequent review reports by our specialist urological pathologists. We also assessed whether a revision in the LS subsequently altered the risk group. Patients and Methods In all, 54 consecutive patients had had their initial histology after nephrectomy reported by a general pathologist between August 2008 and March 2012. The histological slides were subsequently re‐reviewed by the two specialist urological pathologists and revised LS were given if appropriate. The cases were then discussed at the Uro‐oncology Multi disciplinary meeting (MDT) and the reason for the revised LS was discussed with the participating panel and reviewed by the uropathologist. Results The general pathologists allocated the 54 patients into low‐ (13 patients), intermediate‐ (25) and high‐risk (16) categories. After a review of the slides by the specialist urological pathologists and discussion at the MDT meeting the LS was revised in 23 patients (42.6%). The 23 patients who had their LS revised were divided into two groups for the purpose of the present study. On revision of the LS a total of eight patients (14.8%) changed their prognostic group. The change in the prognostic group in the eight patients was increased from intermediate‐ to high‐risk in four patients. There was a reduction in the LS in four patients, which was from high‐ to intermediate‐risk category in one patient and intermediate‐ to low‐risk in three patients. Conclusion In the present study, histopathology review by a specialist urological pathologist led to a change in LS in 42.6% of cases leading a change in risk grouping in 14.8% of cases. This level of discrepancy is not insignificant. However, the few cases evaluated in the present study does limit robust conclusions and further studies are needed to investigate this issue, so that recommendations can be made to enhance diagnostic accuracy and reproducibility.